Ḥadāʼiq al-siyāḥah - Shīrvānī, Zayn al-ʻĀbidīn, 1780-1837 or 1838.; Nuttall, Frank E., 1875-1943 (1857)
Fine copy of a work by Zayn al-ʻĀbidīn al-Shīrvānī (d.1837) relating his extensive travels and Ṣūfic thought, completed in Shīrāz in 1827 before his departure on a final pilgrimage to Mecca, after completion of his Riyāz̤ al-siyāḥah (composed 1237/1821-2) and before completion of his Bustān al-siyāḥah (composed 1248/1833).
Shelfmark: Ann Arbor, University of Michigan, Special Collections Research Center, Isl. Ms. 881
Origin: As appears in scribal colophon on p.586, transcription completed 3 Jumādá I 1274 [ca. 20 December 1857]. As appears in preceding authorial colophon (also on p.586), composition completed in Shīrāz on ʻĪd al-Ghadīr 18 Dhū al-Ḥijjah 1242 [ca. 13 July 1827].
Accompanying materials: a. Scrap with title in ink "Hadīqat as-Siyāḥat" (paginated pp.1-2) -- b. Recycled card with notes in handwriting of Emilie Savage-Smith [?] "Geog. dict. | colophon gives date | rubrication becomes more & more purple the more recent the MS." (paginated pp.3-4) -- c. Slip with note "Persian MSS (Heyworth-Dunne? No Husselman or Meredith-Owens notes" (paginated pp.5-6).
Former shelfmark: Mich. Isl. Ms. temp. no. 30
Binding: Pasteboards covered in tan leather ; Type III binding (without flap) ; board linings and hinges in a teal wove paper ; upper and lower covers carry blind-stamped scalloped mandorla (filled with vegetal composition) and pendants as well as border in blind rules ; small label on spine carries inscription in French "Dict Géographique Persan" ; sewn in dark pink and lime green thread, two stations ; worked chevron endbands in pink and yellow, fairly good condition (tab extends from spine leather) ; overall in somewhat poor condition with lower cover fully detached, some abrasion, staining, lifting and losses of spine leather, etc.
Support: Wove paper ; highly sized and burnished to glossy, dark cream in color.
Keywords: Shīrvānī, Zayn al-ʻĀbidīn, -- 1780-1837 or 1838 -- Travel; Manuscripts, Persian -- Michigan -- Ann Arbor; Middle East -- Description and travel; Islamic countries -- Description and travel